2019
DOI: 10.1159/000500043
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Features that Predict Transplant Glomerulopathy Progression in a Chinese Cohort

Abstract: Background: Transplant glomerulopathy (TG) represents a major cause of long-term allograft failure and is the leading cause of overall post-transplant proteinuria. The extent to which histopathologic features predicts prognostication is uncertain. Methods: A single-center retrospective cohort with biopsy-proven TG was investigated. Renal biopsies were scored according to Banff 2017. The primary outcome was death-censored graft failure defined as return to dialysis or estimated glomerular filtration rate (eGFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
3
5
1
Order By: Relevance
“…Contrary to the results of previous studies, C4d deposition in PTC was identified as a risk factor for proteinuria in TG patients in our study (13,25). Peritubular capillary C4d usually represents active antibody-mediated rejection, all C4d positive patients showed evidence of DSA before the biopsy in our study (33).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the results of previous studies, C4d deposition in PTC was identified as a risk factor for proteinuria in TG patients in our study (13,25). Peritubular capillary C4d usually represents active antibody-mediated rejection, all C4d positive patients showed evidence of DSA before the biopsy in our study (33).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous studies, the severity of proteinuria was significantly correlated with Banff lesion score cg and mm though both of them were not significant in univariable and multivariable logistic regression analysis (13,25,26). This might due to the lower cut-off value for the diagnosis of proteinuria in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Our study provided additional insight into the prognostic value of proteinuria at the time of diagnostic biopsy of TG as well as dynamic proteinuria changes of during follow‐up. The existing studies regarding the influence of proteinuria on the survival of TG patients showed conflicting results, which might be due to the small sample size, the different criteria on patient inclusion and different patient cohorts [7,16–20]. Compared with previous studies, our study excluded patients with secondary TG, such as recurrent/ de novo glomerulonephritis, TMA, and hepatitis C virus‐associated MPGN, which might control the effect of these confounders to improve the reliability of the results [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, within the TG diagnosis, several individual parameters have been associated with graft loss in studies. For instance, time of onset of TG (early vs late), TG severity (by Banff) and amount of proteinuria have all been associated with poor long‐term allograft survival 6,18,50 . Further, differential gene expression of complement cascade, interleukins, granulysin and ENDATs were associated with allograft loss, suggesting that gene expression profiles might help in predicting allograft loss within this syndrome 7 …”
Section: Prognosismentioning
confidence: 99%